2008
DOI: 10.1007/s00431-008-0681-6
|View full text |Cite
|
Sign up to set email alerts
|

Nephrocalcinosis in glucose-galactose malabsorption: nephrocalcinosis and proximal tubular dysfunction in a young infant with a novel mutation of SGLT1

Abstract: We report an association of proximal renal tubular dysfunction in a 50-day-old girl with glucose-galactose malabsorption who was found to have nephrocalcinosis, but no sign of nephrolithiasis. A novel homozygous nonsense mutation at 267Arg-->stop (CGA-->TGA) in the Na(+)-dependent glucose transporter (SGLT1) was found in loop 5 connecting transmembrane segments 6 and 7, indicating the complete loss of glucose transport activity. This case indicates that hypercalcaemia, nephrocalcinosis and proximal tubular dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 9 publications
0
19
0
1
Order By: Relevance
“…Absorbed glucose then diffuses back into the blood from basolateral side of cells via GLUT transporters in a Na + -independent manner (Wright et al, 2011). Humans with mutations in SLC5A1 gene encoding SGLT1 suffer from an intestinal disease known as glucose-galactose malabsorption but have little or no sign of glucosuria (Soylu et al, 2008; Wright et al, 2011; Xin and Wang, 2011). However, people with mutations in SLC5A2 gene encoding SGLT2 develop severe glucosuria (Lee et al, 2012; Santer and Calado, 2010; Yu et al, 2011) with urinary excretions of glucose as high as 160 g per day (Bakris et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Absorbed glucose then diffuses back into the blood from basolateral side of cells via GLUT transporters in a Na + -independent manner (Wright et al, 2011). Humans with mutations in SLC5A1 gene encoding SGLT1 suffer from an intestinal disease known as glucose-galactose malabsorption but have little or no sign of glucosuria (Soylu et al, 2008; Wright et al, 2011; Xin and Wang, 2011). However, people with mutations in SLC5A2 gene encoding SGLT2 develop severe glucosuria (Lee et al, 2012; Santer and Calado, 2010; Yu et al, 2011) with urinary excretions of glucose as high as 160 g per day (Bakris et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Using an animal model, Suzuki et al [33] demonstrated that a gain of function haplotype in TRPV6 plays a role in calcium stone formation in certain forms of absorptive hypercalciuria. This could be a plausible mechanism for the nephrocalcinosis seen in our patients and the cases already reported [4, 7]. Reasons for persistent nephrocalcinosis despite adequate diet are unclear.…”
Section: Discussionmentioning
confidence: 74%
“…Although there are over 40 mutations of SLC5A1 that have been linked to GGM [36], only 2 other patients with nephrocalcinosis and GGM have their mutations described in the literature [7, 8]. Therefore, there are insufficient data for genotype-phenotype associations at this point [18, 36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finding renal abnormalities is also another clue to suspect GGM as the sodium/glucose co‐transporter‐1 is present in both intestinal cells and in renal tubules. Renal abnormalities were reported in association with GGM, namely hematuria, nephrocalcinosis and renal tubular acidosis, rickets, nephrogenic diabetes insipidus, and renal stones. Neonatal irreversible renal failure was not reported before.…”
Section: Discussionmentioning
confidence: 99%